2004
DOI: 10.1165/rcmb.2003-0377oc
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Catalase and Glutathione Peroxidase Activity Dampen H2O2Signaling in Human Alveolar Macrophages

Abstract: Results are presented which support the hypothesis that adequate steady-state levels of hydrogen peroxide (H2O2) are required to overcome the effects of high catalase and glutathione peroxidase (GPx) expression for p38 mitogen-activated protein (MAP) kinase activation and tumor necrosis factor (TNF)-alpha gene expression in human alveolar macrophages stimulated with asbestos. We found significant differences in the types and amounts of reactive oxygen species generated in human blood monocytes compared with hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 78 publications
7
50
1
Order By: Relevance
“…Enzymatic parameters of oxidative stress results in this study showed no significant difference in CAT and GST activity means between the exposed and non-exposed groups (Table 3), nor between individuals exposed without asbestosis and those exposed with asbestosis (Table 4), in contrast to previous observations in the international literature [35][36][37].…”
Section: Group Exposed To Asbestoscontrasting
confidence: 99%
See 1 more Smart Citation
“…Enzymatic parameters of oxidative stress results in this study showed no significant difference in CAT and GST activity means between the exposed and non-exposed groups (Table 3), nor between individuals exposed without asbestosis and those exposed with asbestosis (Table 4), in contrast to previous observations in the international literature [35][36][37].…”
Section: Group Exposed To Asbestoscontrasting
confidence: 99%
“…It is possible that this same effect occurred with the CAT activity too; however, an increase in CAT activity induced by asbestos fibers has been reported in the literature, but did not compare exposed individuals without and with asbestosis [36,37]. Furthermore, a positive statistically significant correlation (p < 0.001, R = + 0.527) was found between the CAT results with GST, using partial correlation, controlled by age, smoking habits and alcohol consumption.…”
Section: Group Exposed To Asbestosmentioning
confidence: 86%
“…It also has been shown that inhibition of catalase by 3-AT increases H 2 O 2 levels in macrophages (54). NO may attenuate H 2 O 2 production by inducing catalase.…”
Section: Discussionmentioning
confidence: 96%
“…For histology sections, similar thymic lobes were fixed in formalin, embedded in paraffin, cut in 5-Am sections, and stained with H&E. In-gel (nondenaturing PAGE) enzyme assay was used to determine the activities of superoxide dismutases (SOD) and catalase. The achromatic band intensities indicated the enzyme activities (27).…”
Section: Methodsmentioning
confidence: 99%